نحو نظرية إيجابية لتلفزيون الطفل بالتطبيق على قناة ماجد - إبراهيم، صفاء عباس عبدالعزيز (المركز العربي للأبحاث والدراسات الإعلامية, 2020)
وجدت الباحثة في أثناء دراستها واطلاعها وكتاباتها عن تلفزيون الطفل أن أ كثر الدراسات لو لم تكن جلها تتناول سلبيات محتوى تلفزيون الأطفال، ولكن حسب تجربة الباحثة مع أطفالها في المنزل ومشاهداتها معهم لاحظت أن المحتويات الإيجابية تكاد تغلب على المحتويات السلبية، وهذا ما دفعها إلى اختيار موضوع الدراسة، والرغبة في تغيير النظرة السلبية لمحتوى البرامج التلفزيونية للأطفال بعنوان: (نحو نظرة إيجابية لتلفزيون الطفل بالتطبيق على قناة ماجد)، وهي من أ كثر القنوات مشاهدة لدى الأطفال. هدفت الدراسة التعرف إلى قناة ماجد والوقوف على محتوياتها ودراسة مدى إيجابياتها وإسهاماتها وتشكيل نظرة إيجابية تجاه محتوى تلفزيون الأطفال ولتحقيق تلك الأهداف رأت الباحثة أن معالجة مشكلة الدراسة تكمن في الإجابة عن الأسئلة الآتية: ما البرامج التي تقدمها قناة ماجد؟ ما القيم الإيجابية لمحتوى برامج قناة ماجد؟ أي القيم أكثر غلبة في البرامج: الإيجابية أم السلبية؟. وترجع أهمية الدراسة إلى قلة الدراسات التي تناولت إيجابيات محتوى تلفزيون الطفل، وتأمل الباحثة أن تضيف هذه الدراسة لبنة جديدة في مجال دراسات المحتوى التلفزيوني بعامة، وتلفزيون الأطفال بخاصة، وتأطر لتشكيل نظرة إيجابية تجاه محتوى تلفزيون الأطفال والاستفادة منها في الدراسات المستقبلية، وخرجت الدراسة بعدة نتائج أهمها: قناة ماجد الفضائية لها برامج الفكرة والمحتوى فيها تهتم بالجانب المعرفي للطفل وتستخدم الرسوم المتحركة، وأحيانا شخصيات حقيقة لتقديم معارف ومعلومات للطفل في شكل أفلام ومسلسلات، الهدف منها هو حماية عقله وسلوكه وقيمه وتنمية مواهبه وصقل قدراته العقلية والبدنية. أن القائمين على أمر القناة لهم دراية تامة بحاجات الأطفال وكيفية جذب اهتمامهم وصمموا برامج ذات محتوى إيجابي مصحوبة بحركات وألوان جذابة توجه الطفل إلى معرفة أشياء وأمور متنوعة، ما كان للطفل أن يجد الفرصة ليتعلمها دون مشاهدة هذه الأفلام والرسوم الكرتونية المتحركة في قناتها. يمكن أن تكون هنالك من السلبيات التي تضر بالطفل إذا لم تكن متابعة وإرشاد من أفراد الأسرة، إ اذا ما أخذناها في الحسبان سلبيات الرسوم المتحركة الأجنبية على الطفل، تكون أحيانا غريبة الصنع والهوية على عقول أطفالنا، لأنها صممت لغير أطفالنا وبعقلية غير عقليتنا وثقافاتنا، ما يجعلها تعلم الأطفال بعض عادات وأخلاق تبعد كثيرا عن عاداتنا وأخلاقياتنا وعقيدتنا ولا تتماشى مع طبيعة مجتمعاتنا العربية كما في برنامجي آرنست وسليت وحماة الأرض بالرغم من احتوائها على الدعوة لبعض القيم الاجتماعية والثقافية الحميدة مثل، الصدق والوفاء، التعاون.
The researcher found during her study, briefing, and writings on children's TV that most studies, if not all of them, deal with the negative aspects of children's television content, but according to the researcher's experience with her children at home and her observations with them, she noticed that positive content almost overcame negative content. The desire to change the negative perception of the content of children's TV programs has prompted her to choose the subject of the study entitled: (Towards a positive view of the children's television by applying on the Majid channel), which is one of the most viewed channels among children. The study aimed to get acquainted with the Majid channel, learn about its content, study the extent of its positives and contributions, and form a positive view towards the content of children's television. To achieve these goals, the researcher saw that the treatment of the study problem lies in answering the following questions: What programs does the Majid channel offer? What are the positive values of the content of Majid channel programs? Which values are more prevalent in programs: positive or negative? The importance of the study is due to the lack of studies that dealt with the positive aspects of child TV content, and the researcher hopes that this study will add a new brick in the field of television content studies in general, and children's television in particular, and it is framed to form a positive view towards the content of children's television and benefit from it in future studies. The study has come out with several results. The most important ones are: Majid satellite channel has programs of idea and content that focus on the child's knowledge side and uses animation, and sometimes real characters to provide knowledge and information to the child in the form of movies and series, the aim of which is to protect his mind, behavior, values and the development to sharpen and refine his mental and physical abilities. Those who are in charge of the channel’s command are fully aware of children's needs and how to attract their attention and design programs with positive content accompanied by attractive movements and colors that direct the child to learn various things. Actually, the child would not have had the opportunity to learn without watching these movies and animated cartoons on its channel. There can be negative impact that harms children if they lack follow-up and guidance from family members, if we take into account the negatives of foreign animation on the child, sometimes they are strange to the extent that they affect the identity and minds of our children, because they are designed for other children and with a mentality other than our child’s mentality and our cultures, which teaches children some habits and morals that are far from our customs, ethics and beliefs and are not in line with the nature of our Arab societies as in the programs of Arnest and Slate and the protectors of the earth, despite the invitation to some social and cultural values such as, honesty, loyalty, and cooperation.
Keywords: الدراسات التربوية -- تلفزيون الأطفال -- المحتويات الإيجابية -- المحتويات السلبية -- قناة ماجد